2021
DOI: 10.1111/apt.16599
|View full text |Cite
|
Sign up to set email alerts
|

Clinical classification and long‐term outcomes of seronegative coeliac disease: a 20‐year multicentre follow‐up study

Abstract: Background: Seronegative coeliac disease is poorly defined. Aims:To study clinical phenotypes and long-term outcomes of seronegative coeliac disease in a multicentre cohort over 20 years.Methods: Seronegative coeliac disease was diagnosed in HLA-DQ2/DQ8-positive patients with villous atrophy (VA), negative IgA endomysial (EmA), tissue transglutaminase (tTG) and deamidated-gliadin antibodies (DGP), clinical and histological response to a gluten-free diet (GFD), and no alternative causes for VA. In patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…Approaching the differential diagnosis of enteropathies characterised by VA and negative coeliac serology is complex, as the underlying causes described in the literature are extremely heterogeneous. Apart from CD presenting with negative serology, VA can be found also in chronic enteropathies unrelated to gluten ingestion, which are often misdiagnosed as seronegative forms of CD 1–3 7–15. Interestingly, VA is the diagnostic hallmark for some of these NCEs, whereas for others, it is only one of the elements contributing to the entire clinical and histopathological picture.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Approaching the differential diagnosis of enteropathies characterised by VA and negative coeliac serology is complex, as the underlying causes described in the literature are extremely heterogeneous. Apart from CD presenting with negative serology, VA can be found also in chronic enteropathies unrelated to gluten ingestion, which are often misdiagnosed as seronegative forms of CD 1–3 7–15. Interestingly, VA is the diagnostic hallmark for some of these NCEs, whereas for others, it is only one of the elements contributing to the entire clinical and histopathological picture.…”
Section: Methodsmentioning
confidence: 99%
“…Although the diagnosis of CD is straightforward in the vast majority of cases, diagnostic challenges can occur when VA is found in patients reporting GI symptoms and testing negative to coeliac specific antibodies 1–3 7. The first step is to ensure that there have been no errors of inadequate sampling, collection or processing of either serum samples or duodenal biopsies, the latter potentially resulting in incorrect orientation and evaluation of duodenal specimens; another key requirement is that the diet has not been gluten restricted prior to endoscopy 1–3 7–9. Thereafter, the clinical scenarios characterised by VA and negative coeliac serology can be broadly attributed to two main clinical entities: CD presenting with negative antibodies and chronic enteropathies unrelated to CD and gluten ingestion, which we have defined as non-coeliac enteropathies (NCEs) 1–3…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the largest study to date involving 227 adult patients previously diagnosed with SNVA, Schiepatti et al found that SNCD had more severe symptoms at diagnosis, nearly 11 times higher risk of complications, and 2 times higher risk of mortality than seropositive CD [15].…”
Section: Seronegative Coeliac Disease (Sncd)mentioning
confidence: 99%